Optical properties and mathematical model for water based alumina and titania nanofluids / Mohammad Sajid Hossain - Hossain, Mohammad Sajid (2013)

(untitled)
The purpose of this research is to experimentally investigate optical behaviour of Alumina and Titania nanofluids. Effects of aggregation on optical properties along with development of a mathematical model for extinction coefficient have also been done. In this dissertation, Classical theories such as, Rayleigh, Quasi Crystalline, Maxwell-Garnett and Lambert-Beer’s approaches are used for analytical analysis. Experiment is conducted for 0.03, 0.05 and 0.08 %v/v concentrations at different time intervals. Outcome of the dependencies are then combined together to obtain a realistic mathematical model for measurement of extinction coefficient. Results of the study show that Alumina nanofluids are very stable for 0.03 %v/v concentration comparative to Titania nanofluids in a basefluid of pH 4 at room temperature. However, extinction coefficient and refractive index of Titania nanofluids are found higher than that of Alumina nanofluids in visible region of light for all concentrations. At the first hour, in the visible region (400-700 nm), extinction coefficient of water (basefluid) was enhanced by Alumina by averagely 5.5, 9.5 and 18.7 times for 0.03, 0.05 and 0.08 %v/v concentrations respectively. On the other hand, at the first hour in the visible region (400-700 nm), extinction coefficient of water (basefluid) was enhanced by Titania by averagely 89.5, 107 and 116 times for 0.03, 0.05 and 0.08 %v/v concentrations respectively. Reductions in extinction coefficients at different stages after preparation are found very low (around 10%) for Titania nanofluids comparative to Alumina nanofluids (around 30%). It is also found that the proposed model gives accuracy more than 65% for Alumina in the range of 350-1100 nm for up to 0.08 %v/v concentration. On the other hand, it can give accuracy more than 72% for Titania nanofluids in the range of 650-1100 nm wavelength for up to 0.05 %v/v concentration. iv As a conclusion, Alumina is found good in the sense of stability. Although optical enhancement of it is lower than that of the Titania, Titania is less stable. Titania may perform as a good solar irradiation absorber if it can be stabilized properly. The proposed model is also a good achievement, since it can give more than 65% accuracy. It is worth mentioning that present available models hardly provide up to 32% accuracy for Titania and the value is even less for Alumina nanofluids. Results of this work will be very helpful in analysing direct absorption solar collectors using Alumina and Titania nanofluids. Other nanofluids can also be investigated for different concentrations and sizes to enrich the data for practical usage and development of new solar energy harvesting technologies, such as direct absorbing solar collectors.